2015
DOI: 10.1016/j.jcrc.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

sTREM-1 predicts intensive care unit and 28-day mortality in cancer patients with severe sepsis and septic shock

Abstract: Patients with cancer have different immune profile in sepsis when compared with patients without cancer, as demonstrated for levels of cytokines, sTREM-1 and HMGB-1. sTREM-1 and days spent in mechanical ventilation proved to be good predictors of ICU and 28-day mortality in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Similarly, AUC of 0.68 (95% CI 0.58–0.78) for sTREM-1 for predicting hospital mortality was observed by Latour-Perez et al (2010). The serum concentration of sTREM-1, but not IL-6 or IL-8, also predicted the ICU mortality and 28-day mortality in cancer patients with severe sepsis and septic shock (Ravetti et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, AUC of 0.68 (95% CI 0.58–0.78) for sTREM-1 for predicting hospital mortality was observed by Latour-Perez et al (2010). The serum concentration of sTREM-1, but not IL-6 or IL-8, also predicted the ICU mortality and 28-day mortality in cancer patients with severe sepsis and septic shock (Ravetti et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were obtained recently in a small cohort of cancer patients. Indeed, Ravetti et al showed that levels of sTREM-1 over time were higher in survivors than in non-survivors [ 17 ]. This may be subsequent to the dual significance of plasma levels of sTREM-1.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of sTREM‐1 at admission could also be used as a marker to identify patients with a poor prognosis as the sTREM‐1 levels in non‐survivors with severe sepsis who even received early goal‐directed therapy after admission remained high until death . In cancer patients with sepsis who might display a more complexed immune profile, the plasma level of sTREM‐1 is still a good predictor of 28‐day mortality . When compared with other biomarkers such as PCT and CRP in predicting survival of patients with septic shock, sTREM‐1 was found to be beneficial .…”
Section: Alteration Of Neutrophil Function In Sepsismentioning
confidence: 99%